E-commerce implication: Potential tax problems and challenges in Malaysia - Mohd Hanefah, Mustafa; Othman, Zaleha; Hassan, Haslinda (Universiti Utara Malaysia, 2006)
The shift in business models to incorporate e-commerce by great expectations of future growth, have naturally attracted the attention of both private sector tax professionals and government tax authorities.With the use of internet as a medium in conducting business transactions, people are now taking the opportunities to expand business has triggered problems to the government in taxing the transactions since there is no physical presence exist, and therefore, creates problems for tax collection.Thus, this study draws attention to the importance of taxing e-commerce transactions and investigates tax problems and challenges posed by e-commerce businesses in Malaysia.A survey approach was conducted in gathering the necessary data.The results show that tax administration is ranked as the highest tax problem posed by e-commerce business in Malaysia and there is no significant difference in the opinion of the subjects in relation to taxing of either tangible or intangible product.In addition, overall findings also reveal that occupation, business nature, and experiences do not influence the subjects' opinions towards e-commerce tax liability in regards to tax problem and legality of claiming taxes in various jurisdictions, and residence-based system appears to be the best solution to solve the problem of internet trading.